2010
DOI: 10.1371/journal.pone.0011199
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Lactobacillus plantarum Expressing Borrelia burgdorferi OspA Is Modulated by the Lipid Modification of the Antigen

Abstract: BackgroundOver the past decade there has been increasing interest in the use of lactic acid bacteria as mucosal delivery vehicles for vaccine antigens, microbicides and therapeutics. We investigated the mechanism by which a mucosal vaccine based in recombinant lactic acid bacteria breaks the immunological tolerance of the gut in order to elicit a protective immune response.Methodology/Principal FindingsWe analyzed how the lipid modification of OspA affects the localization of the antigen in our delivery vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 50 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…1B and C). Lipidation of OspA has been shown to be important for overcoming oral tolerance by inducing a Th1/Th2 immune response (19). Hamsters immunized by oral gavage with E. coli expressing the lipidated LigA7-13 antigen developed a protective immune response to lethal challenge by L. interrogans serovar Copenhageni.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B and C). Lipidation of OspA has been shown to be important for overcoming oral tolerance by inducing a Th1/Th2 immune response (19). Hamsters immunized by oral gavage with E. coli expressing the lipidated LigA7-13 antigen developed a protective immune response to lethal challenge by L. interrogans serovar Copenhageni.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of the 16-amino-acid lipoprotein signal peptide of OspA tags the protein for translocation across the cytoplasmic membrane and subsequent lipidation. Lipidation is known to function as an adjuvant (16)(17)(18), and the immune response to oral immunization with OspA has been shown to be modulated by its lipidation (19).…”
mentioning
confidence: 99%
“…Analysis of localization and lipidation of the five vaccine constructs used in this study revealed that the OspA signal peptide tagged OspC K, OspB, BBK32, Salp15 and Salp25 for translocation across the cytoplasmic membrane, given that these proteins were primarily found in the envelope fraction (>60%) as opposed to the cytosolic fraction of the cell. Furthermore, OspC K, BBK32 and Salp15 constructs partitioned mostly into the detergent phase (Figure 3-1), the hydrophobic fraction of the E. coli cell envelope, consistent with protein lipidation and with our previous findings [110,114,115].…”
Section: Chapter 4 Discussion and Concluding Remarks Discussionsupporting
confidence: 89%
“…Our vaccine technology consisted of recombinant live E. coli expressing the leader sequence of B. burgdorferi OspA lipoprotein fused to the N-terminus of each candidate immunogen (OspC K, OspB, BBK32, Salp15 or Salp25), aiming to target them across the cytoplasmic membrane to the cell envelope as previously shown [110,114,115]. Analysis of localization and lipidation of the five vaccine constructs used in this study revealed that the OspA signal peptide tagged OspC K, OspB, BBK32, Salp15 and Salp25 for translocation across the cytoplasmic membrane, given that these proteins were primarily found in the envelope fraction (>60%) as opposed to the cytosolic fraction of the cell.…”
Section: Chapter 4 Discussion and Concluding Remarks Discussionmentioning
confidence: 99%
See 1 more Smart Citation